POSTMAGMATIC SULPHUR LOSS IN THE SKAERGAARD INTRUSION: IMPLICATIONS FOR THE FORMATION OF THE PLATINOVA REEF - Andersen J.C.O. (My University, 2006)
The stratabound Platinova Au-Pd Reef in the Skaergaard Intrusion is intimately linked to Cu-Fe sulphide minerals and occurs at a level that shows changes in the sulphur concentration and the Cu/S ratio. These features suggest that the reef is related to silicate-sulphide liquid immiscibility in the Skaergaard magma. However, although the evidence is strong, present day sulphur concentrations are too low to support such a model. The detailed knowledge of the shape, volume, and compositional relations of the Skaergaard lithologies allows for numerical modeling of sulphur and copper concentrations during fractionation of the magma. These data can be evaluated with the current models for sulphur saturation in iron-rich mafic magmas to assess the original sulphur concentrations, the extent of fractionation, the composition of sulphide liquids, and the extent of postmagmatic sulphur loss. Mass balance modeling yields initial copper and sulphur concentrations of 250 and 894 ppm for the parental magma to the Lower Zone a. Prior to sulphur saturation, Cu behaves as an incompatible element with a bulk partition coefficient in the cumulus material, DcumulusCu of 0.13 indicating some incorporation of Cu into mafic silicates (probably augite). Sulphur can be assumed to be perfectly incompatible in the cumulus minerals, although it will be included as a component of the interstitial liquid. These values yield sulphur saturation at around 635 ppm Cu and 2607 ppm S. Assuming the sulphur to originally be present as a mixture of monosulphide (MSS) and intermediate solid-solution sulphide (ISS), the primary sulphides in the cumulates would amount to 0.07 modal % through Lower and Middle Zones and 0.53 modal % on average through Upper Zone. The expected weight proportion of primary chalcopyrite / pyrrhotite evolves from 30 : 70 at the base of LZa through 26 : 74 at the level of the Platinova Reef to 18 : 82 at the Sandwich Horizon. The present-day bornite-magnetite mineral assemblage is likely to have been derived from a primary pyrrhotite-chalcopyrite assemblage through reequilibration and postmagmatic oxidation. Significant sulphur appears to have been lost from the lower and middle parts of the Layered Series (Lower Zone a to Upper Zone b), whereas the sulphides of the Upper Zone c can be explained in the context of a sulphur gain. Local-scale reequilibration of Cu from mafic silicates into sulphides may have contributed to the sulphide mineralogy of the Lower and Middle Zones. The structure of the Platinova Reef probably formed from an original single, stratabound reef. Sulphur loss through oxidation in upward migrating deuteric or hydrothermal fluids could have caused dissolution and reprecipitation of Pd and Au in a cumulate with several stratiform redox barriers. This process can thus explain the successive Pd peaks of the reef as well as the variable stratigraphic offset of Pd and Au across the intrusion. © 2006 Elsevier B.V. All rights reserved.
Keywords: GOLD; PLATINOVA REEF; PLATINUM-GROUP ELEMENTS; SILICATE-SULPHIDE LIQUID IMMISCIBILITY; SKAERGAARD INTRUSION; SULPHUR SATURATION